Optical and photoluminescence properties of CaV2O6 functionalized by sodium doping. (June 2021) - Kaur, Paramvir; Singh, Vikramjit; Singh, K.
Abstract: In the present article, sodium-doped calcium vanadate, Ca1- x Na x V2 O6 (0.00≤ x ≤0.10 with a step size of 0.025) is prepared via the solid-state reaction route. Structural, optical and electrical properties are investigated using different characterization techniques. The X-ray diffraction and scanning electron microscopy exhibit a single-phase monoclinic structure of Ca1- x Na x V2 O6 (0.00≤ x ≤0.1) with non-uniform rod-shaped grains, respectively. The optical band gap is in the semiconducting range i.e. 2.25−1.40 eV and decreases with Na2 O (dopant) concentration. The highest photoluminescence intensity is observed for x = 0.075 doped sample with blue luminescence. Impedance spectroscopy results show that the conductivity of the samples increases with the increase in the dopant concentration. The change in the oxidation state of vanadium and doping of sodium facilitate the conduction process in the present samples.